Implikasi Hukum Terhadap Akta Yang Dibuat Pejabat Pembuat Akta Tanah Yang Dibatalkan Oleh Pengadilan - Sari, Rieka Anita (Universitas Sang Bumi Ruwa Jurai, 2025)
This paper aims to analyse the legal implications on deeds made by officials who make land deeds that are canceled by the court (Case Study of Tangerang District Court Decision No. 473/Pdt.G/2019 concerning Cancellation of Dependent Rights). The cancellation of the deed by the court can have significant legal consequences for various parties, including PPAT, parties involved in the transaction, and interested third parties. The research method used is normative juridical with a case approach. The results of the study show that the cancellation of deeds by the court is generally caused by various factors, such as legal defects in the making of deeds, violations, procedures, or fraud committed by PPAT or related parties. The implications of the cancellation include material losses for the parties involved, a decrease in public confidence in the credibility of PPAT, and the potential for further lawsuits against PPAT. The cancellation of this deed also has an impact on the legal status of transactions made under the cancelled deed, as well as affecting the legal rights of third parties who may not be directly involved in the case but are affected by the court decision